Transmission mechanisms in HANK: An application to Chile - Benjamín García; Mario Giarda; Carlos Lizama; Ignacio Rojas (Latin American Journal of Central Banking (LAJCB), 2024)
Households in emerging economies are subject to significant income risk and have low access to financial markets. Leveraging multiple administrative microdata sources, this paper documents significant heterogeneity in asset holdings, income, and income cyclicality across the distribution of Chilean households, as well as considerable income risk. Considering this evidence, we compare the transmission mechanisms between Heterogeneous-Agent New-Keynesian models with search and matching (SAM) and sticky wage frictions (SW), and between one-liquid-asset (OA) and two-asset (TA) specifications. We propose a decomposition of consumption responses into direct, indirect, average, and cross-sectional effects. We show that the transmission mechanisms depend on the labor market setup: in SAM-OA the transmission operates through average and direct effects, while in SW-OA it is through cross-sectional effects. Assets also matter, the transmission in the SW-TA has stronger direct and average effects than SW-OA.
Keywords: D14; D31; E21; 330; Consumption; Business cycles; Heterogeneous agents; Search and matching; Fiscal and Monetary policy